2022
DOI: 10.1186/s12913-022-08223-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health clinicians’ perceptions of nature-based interventions within community mental health services: evidence from Australia

Abstract: Background Mental health conditions are one of the largest burdens of disease in Australia and globally. There is a need to seek innovative and alternative interventions that can prevent and alleviate mental health symptoms. Nature-based interventions (NBIs), namely programs and activities where individuals engage with natural environments with the aim of improving their health and wellbeing (e.g., nature walking groups), may be such an alternative. This study aimed to explore the perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Consumers are usually granted a weekly or fortnightly session with a mental health professional to address their symptoms and concerns. Recent research (Tambyah et al, 2022) has shown that numerous mental health clinicians have advocated for NBIs as an adjunct to medical and talking therapies that would entice consumers who struggled with regular sit-down therapy, taking medications, and leaving the house. As this study's ndings demonstrate, the presence of clinicians, however, ensured the mental health recovery orientation of NBIs and support in the consumers' recovery journey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers are usually granted a weekly or fortnightly session with a mental health professional to address their symptoms and concerns. Recent research (Tambyah et al, 2022) has shown that numerous mental health clinicians have advocated for NBIs as an adjunct to medical and talking therapies that would entice consumers who struggled with regular sit-down therapy, taking medications, and leaving the house. As this study's ndings demonstrate, the presence of clinicians, however, ensured the mental health recovery orientation of NBIs and support in the consumers' recovery journey.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reasonably clear evidence of mental health bene t and now demonstrably strong interest in NBIs among people experiencing high psychological distress, loneliness, burnout and poor sleep (Astell-Burt et al, 2023), few studies have been conducted with people who have diagnosed mental illnesses (Adevi et al, 2018;Picton et al, 2018). A recent study in Australia demonstrated that mental health clinicians were supportive of and willing to recommend NBIs as they believed that it would enhance the consumers' mental wellbeing, social connections, mindfulness, and relaxation (Tambyah et al, 2022). Consequently, this project partnered with the Illawarra Community Mental Health Rehabilitation Service [hereafter 'the Service'] to implement a Nature Walking Group [hereafter NWG] and learn about the experiences of the mental health consumers who participated in the group.…”
Section: Introductionmentioning
confidence: 99%
“…In a highly urbanised world with a disrupted relation to nature, this kind of evidence could be groundbreaking and motivate broad implementation of NbS across regions. Proof of a cause-effect relationship could also serve to reduce scepticism within the medical establishment and support the use of NbS in health care 36,57 . This would likely result in increased awareness in policy and decision-making, leading to better acceptance of NbS for several health challenges.…”
Section: Human Healthmentioning
confidence: 99%
“…Furthermore, while evidence suggests that green social prescriptions are likely to be cost-effective for individuals with mild to moderate mental illness [46]; further research is required to demonstrate the magnitude of these benefits and the potential social and wider returns on investment. It is also reported that while mental health clinicians perceive nature-based interventions to provide a range of health benefits for individuals with mental illness including improved mood, wellbeing, and social connections; there are concerns over barriers to use of services, such as individuals’ mental health symptoms, lack of motivation and geographical accessibility [47,48]. These barriers need to be overcome in order to increase accessibility and uptake of green social prescriptions for the prevention and treatment of mental illness.…”
Section: Green Social Prescribing For Mental Health and Mental Illnessmentioning
confidence: 99%